Associations between first true leaf physiology and seedling vigor in cotton under different field conditions. Issue 1 (27th February 2020) - Virk, Gurpreet; Snider, John L.; Pilon, Cristiane
Abstract: Rapid development of the first true leaf has been suggested as a key driver of seedling vigor in cotton, yet studies demonstrating an association between first true leaf physiological processes and early season cotton growth are limited. It was hypothesized that both first true leaf area (FTLA) and photosynthetic rates would be positively associated with cotton ( Gossypium hirsutum and G. barbadense ) seedling vigor, and that photosynthetic component processes would differ in their contribution to net photosynthesis (An ) of the first true leaf. To test these hypotheses, three different cotton cultivars were planted in the 2017 and 2018 seasons on three selected dates each year to generate broad differences in seedling vigor. Growth analysis was conducted to assess seedling vigor at 3 and 5 wk after planting, and a combination of dark‐ and light‐adapted gas exchange and fluorescence measurements were performed on the first true leaf, concurrent with growth assessments. Seedling vigor was much more strongly associated with FTLA than An on a per unit leaf area basis, suggesting that FTLA was a stronger indicator of seedling vigor. Correlation analysis between An and a number of component processes derived from combined gas exchange and fluorescence measurements indicated that An was strongly correlated with electron transport rates and stomatal conductance. However, we suggest that most of the variability we observed in An of the first true leaf was primarily driven by nonstomatal factors, since no significant correlations between An and chloroplast CO2 concentration or substomatal CO2 concentration was apparent.